DIFFICULTY AND DISCRIMINATION ANALYSIS OF END OF TERM MULTIPLE-CHOICE QUESTIONS AT COMMUNITY MEDICINE DEPARTMENT, WAH MEDICAL COLLEGE - Ramzan, Musarat; Khan, Khola Waheed; Bibi, Saana; Imran, Shezadi Sabah (Pakistan Armed Forces Medical Journal, 2021)
Objective: To perform post analysis of multiple-choice questions given in the 2nd term and send up examinations of the years 2016 to 2018, to establish relationship between difficulty (DF) and discrimination indices (DI) and to find out significant mean difference between the two.Study Design: Cross sectional study.Place and Duration of Study: Community Medicine Department, Wah Medical College, Wah, from Nov 2018 to Mar 2019.Methodology: A total of 390 Multiple-Choice Question of second term and send-up were taken for the study from the year 2016, 2017 and 2018. The response sheets were assessed by Optical Machine Reader (OMR) and the level of difficulty, power of discrimination and reliability were obtained. The data was entered in SPSS version 22.Results: A total of 315 test items were included. Results of the study showed that the reliability (KR20) for all the examined items was in the acceptable range i.e. ≥0.7 and there was no association was found between difficulty index and year p=0.310. The mean difficulty index was found to be 0.48 ± 0.22 and discrimination index as 0.24 ± 0.14.Conclusion: The analysis of 390 test items showed that most of the questions were acceptable in terms of difficulty and discrimination. There is still a need to modify and improve the testing ability of the MCQs with negative discrimination and higher difficulty index.